Implementation of Islamic Education Values in Building Students' Religious Character through an Affective Approach Based on the Qur'an - Lili Sholehuddin Badri; Ahmed Abdul Malik (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Islamic education is a strategic vehicle and an urgent variable for preparing excellent and high-quality human resources. However, it is currently experiencing weakening due to the storms and waves of globalization. Accordingly, it requires effective and sustainable handling. Purpose – This article is one of the creative efforts that aims to build the attitudes of students in elementary schools with religious character through the implementation of Islamic education values with an affectionate approach that is polite, gentle, caring, and compassionate based on the Qur'an. Design/method/approach – This research method was descriptive qualitative, as library research. Data sources were books, teaching materials, journals, and other relevant information. The data was analyzed using critical text analysis techniques. The data collection technique was documentation. Findings – The research has shown that implementing the Islamic education values of affection approach can build students' religious character through 1) the use of learning methods of affection, tenderness, and attention inherent in educators. 2) the use of learning styles of affectionate Islamic education values reflected in attitudes, interests, morals, values, and self-concepts that are passionate, enthusiastic, and fun. 3) the application of learning Islamic education values through habituation, imitation, and appreciation patterns embodied by educators. Research Implications/limitations – This research can have implications for teachers' teaching methods in instilling the values of compassion, care, and gentleness in face-to-face learning in the classroom. Originality/value – Integrating the three elements of affective value reconstruction simultaneously in the learning process can improve students' academic achievement, religious awareness, and good behavior.